Natural Tourist Places of Intag as a Didactic Resource to Improve Reading Skills in Senior Students at Unidad Educativa Cuellaje, Academic Period 2022- 2023 - Puma Angulo, Deysi Cristina (2024)
Develop an academic guide about natural tourist places of Intag, incorporating effective strategies to improve reading skills in senior students at Unidad Educativa Cuellaje.